MINIMALIST LIFESTYLE OF LYFE WITH LESS COMMUNITY AS EFFORT TO MAINTAIN A SUSTAINABLE ENVIRONMENT - Amal Taufiq; Mohd Zainizan Sahdan; Qurrota A’yun (Jurnal Analisa Sosiologi, 2025)
This study was carried out with the intention of discovering the minimalist lifestyle of members of the Liyfe With Less Community in their everyday activities and their efforts to protect the environment. The research approach utilized is netnography, which involves examining the culture of a specific group or community virtually by leveraging information gathered through digital platforms. Data gathering was conducted through netnographic observation, interviews, and documentation, while data analysis employed Max Weber's social action theory. The findings of the study indicate that members of the Lyfe With Less Community practice a minimalist lifestyle through decluttering, utilizing items until they are finished or worn out, making thoughtful consumption choices, and opting for products made from eco-friendly materials. A minimalist approach positively influences the environment. First, it decreases waste generation by adopting mindful consumption habits. Second, it fosters a sustainable lifestyle through the use of eco-friendly products. Third, it minimizes the carbon footprint by embracing the principle of living "just enough. Fourth, it encourages the shift from a linear economy to a circular economy, which emphasizes the use of sustainable and environmentally considerate materials.